Organizational Citizenship Behavior: The Other Side of the Coin - ERBAY, ELİF ÖZGE; Üçok, Dilay Işılay (Marmara Üniversitesi, 2022)
The study aims to discover the probable roles of cultural characteristics in the relationship between organizational citizenship behavior (OCB) and workplace ostracism which is a critical phenomenon among employees. It was designed in a causal model claiming that there are moderating effects of collectivism and belief in collective emotions in the relationship between OCB and workplace ostracism. 309 employees were included randomly in Turkey, and correlation and regression analyses were conducted to test the hypothesis. Unlike similar studies and the expected relationship in our hypotheses, OCB and workplace ostracism were found negatively correlated. Moreover, neither organizational collectivism nor employees’ belief in collective emotions had a moderating role in this relationship. The study showed that the dark side of the OCB does not work for the Turkish culture, although its collectivist features. It is evident that globalization makes the collectivist organizations’ strict norms and rules more flexible and loosens the employees’ collectivist beliefs. Regardless of the cultural characteristics, the study also underlines that workplace ostracism should be prevented with appropriate management strategies like encouraging employees to be engaged in citizenship behaviors.

Bu çalışmada, örgütsel vatandaşlık davranışı (ÖVD) ile çalışanlar arasında kritik bir olgu olan işyeri dışlanması arasındaki ilişkide kültürel özelliklerin olası rollerini ortaya çıkarmayı amaçlamaktadır. Bu nedenle, ÖVD ile işyerinde dışlanma arasındaki ilişkide, kolektivizm ve kolektif duygulara inancın düzenleyici etkileri olduğunu varsayan nedensel bir model tasarlanmıştır. Türkiye’de çalışan 309 kişi kolayda örnekleme yöntemiyle seçilmiş ve anket uygulaması gerçekleştirilmiştir. Literatürde bulunan çalışmalardan farklı olarak, ÖVD ile işyerinde dışlanma arasında negatif korelasyon bulunmuştur. Bunun yanı sıra, kolektivizm ve çalışanların kolektif duygulara olan inançlarının bu ilişkide herhangi bir düzenleyici rol üstlenmediği ortaya çıkmıştır. Çalışma, örgütsel vatandaşlık davranışının karanlık yüzünün kolektivist özelliklere sahip olmasına rağmen Türk kültürü için geçerli olmadığını göstermesi açısından önemli görülmektedir. Küreselleşmenin, kolektivist örgütlerin katı norm ve kurallarını daha esnek hale getirdiği ve çalışanların kolektivist inançlarını gevşettiği açıktır. Aynı zamanda bu çalışmada, kültürel özelliklerden bağımsız olarak, işyerinde dışlanmanın önlenmesine yönelik olarak, çalışanların örgütsel vatandaşlık davranışlarına yöneltecek birtakım yönetim uygulamalarının önerildiği görülmektedir.
Örgütsel Vatandaşlık Davranışı: Madalyonun Diğer Yüzü
▪ JEL Classification: M10, M12.
Keywords: Organizational Citizenship Behavior; Workplace Ostracism; Collectivism